Electronic Judicial Procedure as an Element of Access to Justice Regarding Protection of Rights of Individuals: Legal, administrative, Theoretical and Informational Aspects - Kulinich, Olha; Leheza, Yevhen; Zadyraka, Nataliia; Taranenko, Kseniia; Kostiuk, Tetiana (Jurnal Cita Hukum, 2023)
The purpose of the research is to consider electronic judicial procedure as an element of access to justice regarding protection of rights of individuals. Main content. It has been established that that certain elements of digitalization of social processes change the social space and, in particular, the mechanisms of judicial proceedings. In the process of the development of society, certain factors came to life and these factors led to the growth of the role of information, and therefore to a clearer allocation of the information function in the field of jurisprudence. Development of society and science requires introduction of new technologies into the judicial system of Ukraine. Methodology:  The methodological basis of the research is presented as comparative-legal and systematic analysis, formal-legal method, interpretation method, hermeneutic method as well as methods of analysis and synthesis. Conclusions. The following conclusion was made that the need to use information technologies in the judiciary is due to the global informatization of the modern society, the development of new forms of interaction in the civil sphere with the use of electronic means of communication: the global Internet, mobile and satellite communication systems, etc. “Electronic justice” involves the use of information and communication technologies in the process of implementing procedural legislation. The novelties of the judicial system are aimed at expanding accessibility of justice in conditions of territorial peculiarities of the Ukrainian state, improving the quality of the process and efficiency, achieving transparency and openness of the judicial system.Key words: electronic judicial procedure, access, justice, protection, rights of individuals.